2022
DOI: 10.1016/j.jcyt.2020.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells: a new front emerges in coronavirus disease 2019 treatment

Abstract: Currently, treating coronavirus disease 2019 (COVID19) patients, particularly those afflicted with severe pneumonia, is challenging, as no effective pharmacotherapy for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) exists. Severe pneumonia is recognized as a clinical syndrome, characterized by hyper induction of proinflammatory cytokine production, which can induce organ damage followed by edema, dysfunction of air exchange, acute respiratory distress syndrome, acute cardiac injury, secondary in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…Many clinical trials are conducted over the world to treat inflammation with MSCs, but there is only one stem cell therapy approved in the USA, by the FDA, to treat patients having blood production problems. For the past year, recent studies have been working and testing on using MSCs for COVID-19 treatment, based on MSC/MSC extracellular vesicles antiinflammatory properties [154][155][156]. However, in other cases, the inflammatory reaction could decrease the efficacy of the MSC treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Many clinical trials are conducted over the world to treat inflammation with MSCs, but there is only one stem cell therapy approved in the USA, by the FDA, to treat patients having blood production problems. For the past year, recent studies have been working and testing on using MSCs for COVID-19 treatment, based on MSC/MSC extracellular vesicles antiinflammatory properties [154][155][156]. However, in other cases, the inflammatory reaction could decrease the efficacy of the MSC treatment.…”
Section: Methodsmentioning
confidence: 99%
“…In quick response to the COVID-19 pandemic, MSCs are being utilized in several clinical trials studying SARS-COV2-induced pneumonia [106]. For instance, Zikuan Leng et al have recently reported that the transplantation of MSCs, that do not express ACE2 and TMPRSS2, had improved pulmonary function among other parameters in COVID-19 patients [107].…”
Section: Covid-19mentioning
confidence: 99%
“…In COVID-19 patients, IV administration of MSCs leads to the upregulation of neutralizing chemokines IL-10 and IL-17, and rejuvenates and regenerates the repaired parenchymatous pulmonary tissue through neoangiogenesis. [87][88][89] Hence, the patient will have an improved pulmonary function, compliance, and recovery from COVID-19 pneumonia.…”
Section: Route Of Administrationmentioning
confidence: 99%
“…100 MSCs are bestowed with homing ability, immune-regulatory nature, anti-inflammatory effects, multilineage differentiation potential, and lack of ACE2 and TMPRSS2 receptors. 41,88,89 MSCs are innately immune to SARS-CoV-2 infection as they lack key entry points. 70,101 Immunomodulatory and regenerative potential of MSCs promote repair, regeneration, and rejuvenation of pulmonary parenchymal cells, and also resist necroapoptosis and fibrosis of damaged pulmonary parenchymal tissues, which make MSCs a novel therapeutic option in the inflammatory or late stage of the disease.…”
Section: Plausible Combination Of Cp + Msc For Covid-19mentioning
confidence: 99%